Elements for designing a strategy to support the creation of academic spin-offs in Costa Rican public universities - Monge-A., Mauricio (2016)
This paper presents the results of the determinants about the creation of academic spin-off in public universities in Costa Rica. Case methodology was used and the theoretical framework developed by O`Shea, RP, Chugh, H, and Allen, T (2008) about the determinants of the spin-off academic. The information was collected through personal interviews of the public universities of Costa Rica (UCR, UNA and ITCR) and consultation of secondary sources to collect the data necessary. It was found that the entrepreneurial factor academia is by far the transcendental factor, determining institutional, organizational and external resources have weaknesses that make it difficult the emergence of Spin-off academic, so it is generally concluded that the environment in the public universities of Costa Rica, is unfavorable to the academic enterprise. Is required to improve the quantity and quality of research in engineering, allocate more funds for research in these areas, promote linking academic researchers with the productive sector to increase applied research and externally funded, more flexible legal framework to provide a more favorable environment for entrepreneurship in academic spin off university environment; and have sources of venture capital. This article contributes to decision makers with supportive elements to design a strategy that encourages the creation of academic spin off in public universities in Costa Rica.